The grand design - Hawking, Stephen, 1942-2018 (Bantam Books, 2010)
Along with Caltech physicist Mlodinow (The Drunkard's Walk), University of Cambridge cosmologist Hawking (A Brief History of Time) deftly mixes cutting-edge physics to answer three key questions: Why is there something rather than nothing? Why do we exist? Why this particular set of laws and not some other? Scientists are approaching what is called "M-theory," a collection of overlapping theories (including string theory) that fill in many (but not all) the blank spots in quantum physics. This collection of theories is known as the "Grand Unified Field Theories."